2017
DOI: 10.1007/s00380-017-1037-9
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of moderate hypothermia versus deep hypothermia anesthesia on brain injury during Stanford A aortic dissection surgery

Abstract: This study aimed to compare the effects of moderate versus deep hypothermia anesthesia for Stanford A aortic dissection surgery on brain injury. A total of 82 patients who would undergo Stanford A aortic dissection surgery were randomized into two groups: moderate hypothermia group (MH, n = 40, nasopharyngeal temperature 25 °C, and rectal temperature 28 °C) and deep hypothermia group (DH, n = 42, nasopharyngeal temperature 20 °C, and rectal temperature 25 °C). Different vascular replacement techniques includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Emergency surgeries, including aortic dissection, are essentially an independent risk factors which contributes to poorer outcomes. 44,45 Thus, a true comparison could not be made in our study due to difference in aortic pathologies.…”
Section: Discussionmentioning
confidence: 94%
“…Emergency surgeries, including aortic dissection, are essentially an independent risk factors which contributes to poorer outcomes. 44,45 Thus, a true comparison could not be made in our study due to difference in aortic pathologies.…”
Section: Discussionmentioning
confidence: 94%
“…Then a preliminary screening was made by reading titles and abstracts, and next the full texts were downloaded and assessed for eligibility. Eleven studies [21][22][23][24][25][26][27][28][29][30][31] were finally included. Search flow diagram of the present meta-analysis was depicted in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Three studies were multicentric 22,25,31 and four only included aortic dissection patients. 21,26,28,29 Four studies 21,26,29,30 reported the two groups had the same surgeons, and six 21,22,[24][25][26]30 showed the surgical techniques were similar in the two groups.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Recently, moderate hypothermia (MH) (25-28 C) due to anesthesia has been encouraged by some scholars. 18,19 Future studies should investigate if MH is better for the reduction of the risk of neurological disorders and other complications than DH in this type of population. No neurological complications occurred in this patient case after 6 months of follow-up.…”
Section: Perioperative Management For High-altitude Inhabitantsmentioning
confidence: 99%